Experimental full wavefield reconstruction and band diagram analysis in a single-phase phononic plate with internal resonators. (7th July 2021) - Kherraz, N.; Radzieński, M.; Mazzotti, M.; Kudela, P.; Bosia, F.; Gliozzi, A.S.; Misseroni, D.; Pugno, N.M.; Ostachowicz, W.; Miniaci, M.
Highlights: Combined numerical-experimental approach for the characterization of a 3D metamaterial plate. Novel type of resonator-like geometry exhibiting a full BG, and a high degree of isotropy. Measurement of the out-of-plane full-field through SLDV Experimental reconstruction of the dispersion band diagram Efficient and frequency-selective wave attenuation performance after few unit cells. Abstract: Research on phononic crystal architectures has produced many interesting designs in the past years, with useful wave manipulation properties. However, not all of the proposed designs can lead to convenient realizations for practical applications, and only a limited number of them have actually been tested experimentally to verify numerical estimations and demonstrate their feasibility. In this work, we propose a combined numerical-experimental procedure to characterize the dynamic behavior of metamaterials, starting from a simplified 2D design to a real 3D manufactured structure. To do this, we consider a new design of a resonator-type geometry for a phononic crystal, and verify its wave filtering properties in wave propagation experiments. The proposed geometry exploits a circular distribution of cavities in a homogeneous material, leading to a central resonator surrounded by thin ligaments and an external matrix. Parametric simulations are performed to determine the optimal thickness of this design, leading to a large full band gap in the kHz range. Full-field experimental characterization of the resulting phononic crystal using a scanning laser Doppler vibrometer is then performed, showing excellent agreement with numerically predicted band gap properties and with their resulting effects on propagating waves. The outlined procedure can serve as a useful step towards a standardization of metamaterial development and validation procedures.